PEMODELAN PENGISIAN PULSA LISTRIK PRABAYAR BERBASIS SHORT MESSAGE SERVICE (SMS) - Rahmad Syahputra; Novriyenni Novriyenni; Akim Manaor Hara Pardede (STMIK KAPUTAMA, 2020)
Smart Electricity or probaya electricity is a government program. Electricity is the main need of the community, without electricity, the economy is totally stuck, because many large factories and industries use electricity and depend on electricity. Prepaid kWh meter is one of the innovations that has been carried out by PLN in order to facilitate service to the community. Where the customer must pay in advance for the electrical energy that will be used, so that the use of electrical energy can be controlled by the customer according to their needs and abilities. People buy credit / electricity tokens then input the token code into Prepaid Meters (MPB), MPB automatically reads the serial token number and displays the number of kWh according to the amount purchased. The problem that often arises is the impractical process of inputting the token serial number into the MPB. This study made a SMS-based prepaid electricity charging model. The design of this MPB has three general parts, namely Modems that will message the homeowners, volt meter and ampere meter sensors to detect electrical power, and the brain, which is the microcontroller part of ATMega8535. This microcontroller will control all the running of the system contained in this MPB system. That is controlling the input system in the form of sensors, controlling the modem as a message reminder, controlling the input of electric current.